Finite element simulations of the doublediaphragm forming process: Comparisons with experimental trials - Yu, Xiaobo; Ye, Lin; Mai, Yiu-Wing; Cartwright, Bruce; McGuckin, Damian; Paton, Rowan (European Journal of Computational Mechanics, 2005)
This document provides a comprehensive evaluation of finite element simulations of double diaphragm forming of CF/EP plain weave prepreg. The simulations were performed using the PAM-FORM software, and incorporated critical advances recently achieved in composite forming simulations. The material properties were obtained from characterization tests, or estimated in conjunction with rationalization analyses. By using only one set of material and simulation parameters, the best-match simulations correlate well with all four experimental trials of different setups, which include one good and one wrinkled forming trail of rudder rib shape, and one good and one wrinkled forming trial of a simple cup shape. The simulations also highlight the effects of contact penalty, and the sensitivity to inter-ply friction, and re-confirm the necessity to scale-up the measured intra-ply shearing stiffness.